CUE-LEARNING AND PROBLEM-LEARNING STRATEGIES IN NORMAL AND RETARDED CHILDREN. - Achenbach, Thomas; Zigler, Edward (Child Development, 1968)
A distinction between 2 degrees of reliance upon situational cues in problem solving in proposed. The distinction is formulated in terms of 2 contrasting learning strategies: (1) the cue-learning strategy, which involves heavy reliance upon situational cues, and (2) the problem-learning strategy, which involves active attempts to educe abstract relationships among problem elements. Experiment I demonstrated that retardates could learn a 3-choice relative-size discrimination as quickly as normals of the same MA. However, when an obvious but somewhat misleading cue was provided, retardates relied on the cue significantly longer than normals. Noninstitutionalized retardates relied on the cue significantly longer than institutionalized retardates. Experiment II replicated the results of Experiment I and also demonstrated that reliance on the cue by retardates involved an inhibition of learning rather than caution in responding. Tentative evidence was found that persistent success experiences and reinforcement for independent thought could lead retardates to give up reliance on the cue as quickly as normals of the same MA. Experiment III showed that there was a significant correlation between imitativeness and cue learning in retardates but not in normals.